Improving the Aesthetic Function of Parks at Mokopido Regional Hospital: A Study on the Role of Landscape in Improving Visitor Comfort - Ali, Moh. Mudassir; Pahude, Mansur S. (LPPM Universitas Madako Tolitoli, 2025)
The phenomenon at Mokopido Hospital shows that the park in the hospital environment is less attractive, causing visitors to tend to ignore the park. This can reduce comfort and relaxation functions for patients and visitors who use the park as a green open space. This study aims to improve the aesthetic function of the park at Mokopido Hospital by assessing and optimizing existing landscape elements so that visitor comfort can improve. This study uses qualitative analysis with a direct observation approach and literature studies on park design in the hospital area. Data processing techniques involve identifying important elements in the landscape and linking them to park design theories that support the comfort and beauty of open spaces. The results of the study indicate that park elements such as lighting, vegetation, and walkway design can be improved to create a more attractive and comfortable atmosphere for visitors, as well as support patient healing by creating a space that is more in tune with nature.